2011
DOI: 10.1186/1749-8090-6-68
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical resection of infected left atrial myxoma in a case complicated with disseminated intravascular coagulation and multiple cerebral infarctions: case report

Abstract: Cardiac myxoma is the most common primary cardiac tumour, but infected cardiac myxoma is relatively rare. Infected cardiac myxoma is very fragile, and has a potential to lead to catastrophic disorder with systemic bacteremia, systemic mycotic embolism, and disseminated intravascular coagulation (DIC).We present here the successful surgical treatment of a case of infected left atrial myxoma with septic shock, DIC and cerebral infarction without hemorrahage. Collective review of 58 reported cases with infected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Nineteen (14.3%) patients had other than cerebral artery embolisms, with systemic multiple emboli in 4 (21.1%) [ 55 , 63 , 71 , 80 ] , peripheral multiple emboli in 3 (15.8%) [ 19 , 72 , 85 ] and solitary arterial embolus in 12 (63.2%) patients [ 9 , 11 , 13 , 16 , 21 , 35 , 41 , 43 , 60 , 76 , 84 ] . The 39 affected arteries in 18 patients were listed in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen (14.3%) patients had other than cerebral artery embolisms, with systemic multiple emboli in 4 (21.1%) [ 55 , 63 , 71 , 80 ] , peripheral multiple emboli in 3 (15.8%) [ 19 , 72 , 85 ] and solitary arterial embolus in 12 (63.2%) patients [ 9 , 11 , 13 , 16 , 21 , 35 , 41 , 43 , 60 , 76 , 84 ] . The 39 affected arteries in 18 patients were listed in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, the tumour mass can become friable, with associated bacteraemia, systemic embolism and/or disseminated intravascular coagulation. Polymorphonuclear infiltration of the tumour may be evident and Gram‐staining of the infected portion can reveal the presence of bacteria …”
Section: Gross Pathologymentioning
confidence: 99%
“…As pre-operative attempts failed to correct DIC, aneurysmal surgery was performed despite uncorrected coagulopathy. Yoshioka et al [6] reported a 52-year-old male who presented with DIC complicating infected left atrial myxoma. Septic embolization from the tumour necessitated an emergency open cardiac surgery to remove the tumour.…”
Section: Discussionmentioning
confidence: 98%